Awareness on Oral Hygiene and Practices among General Population - Vignesh.S1 , Archana Santhanam2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
India is the sixth biggest country by area and is the second-most populous country. Factors contributing tothe steady rise in prevalence of oral disease include poor oral health awareness and practice among fellowpeople. Oral health knowledge is considered to be an essential prerequisite for health-related behavior,although only a weak association exists between knowledge and behavior. Keeping a healthy oral profilerequires joint efforts from the dentist as well as the patient himself. The study aims to analyze knowledgeand awareness of oral hygiene and practice among the general population A descriptive cross sectionalsurvey was conducted among 100 patients, visiting a private dental institution, Chennai, through a selfadministered questionnaire. The responses were collected, tabulated in excel sheet and analysed using SPSSsoftware. 97% of the participants were using brush with hard bristles. 81% changed their toothbrush. 40%of the subjects visited a dentist when they were in pain. This shows very less care about oral hygiene whichleads to the future undesirable outcome. This study concludes that there is an urgent need for comprehensiveeducational programs to promote good oral hygiene and impart education about oral hygiene practices.